Uspješnost prognoza vremena za cestovni promet - Sijerković, Milan; Kisegi, Mihovil (Promet - Traffic&Transportation, 2012)
The paper deals with a review of efficiency of ultra short- term and short-term weather forecasts designed for motor traffic. On the pattern of local forecasts for the region of the City of Zagreb in the winter season of 1992/1993 the authors perform the assessment of accuracy of predicted precipitation in general, snow, snowfall and new snow layer of 5 cm and more, glaze, and minimum and maximum air temperature. The assessment of weather conditions has been completed by method of alternation while the assessment of air temperature has been completed by statistic methods congruent with physical scale values. General efficiency of prediction of all mentioned weather aspects has been satisfactory, despite the fact that forecasts are still being made by subjective methods. More successful have been the forecasts referring to the absence of a phenomenon important for motor traffic than those referring to its presence. This comes as a result of the subjective element in provision of forecasts. Forecasters have consciously over-emphasized the possibility of presence of some adverse weather condition in order to avoid joint responsibility for consequences at the time of its occurrence without being predicted or announced. Nevertheless, forecasts have proven to be useful for more efficient and more economic operations of The Winter Road Service in the metropolitan area of Zagreb.